TRIS’S EGO DEFENSE MECHANISM IN NEIL BURGER’S DIVERGENT MOVIE SCRIPT 2014 : A PSYCHOANALYSIS - Dwi Fatmawati; Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2020)
This paper aims to analyze the ego defense mechanism found in the main female character in the Divergent movie script directed by Neil Burger. Divergent is an interesting movie, telling about five factions in the life of humans. This concept makes the audience imagine what if the five factions exist in the real world. This movie presents anxiety experienced by Tris as the main female character. Tris is a divergent person, characterized as having more than one nature. With this characteristic, her life is threatened by the society around as she is considered ‘dangerous’. The research only focused on the defense mechanism employed by Tris to cope up with the anxiety in her life. This research used qualitative methods to reveal Tris’ anxiety and her defense mechanism based on a psychoanalytical theory by Sigmund Freud especially that of anxiety theory. The findings show that Tris undergoes two types of anxiety in this movie script, realistic anxiety and moral anxiety on which to perform featuring five types of ego defense mechanisms, namely Displacement, Reaction formation, Sublimation, Repression, and Regression. Keywords: psychoanalysis, anxiety, ego defense mechanism, divergent